The Effect of Workload and Compensation on Turnover Intention Through Job Satisfaction As a Mediating Variable at PT Aerofood ACS Denpasar - Ni Putu Angelyani Sugiantari Putri; I Wayan Wirga; Ayu Mirah Kencanawati (Digital Innovation : International Journal of Management, 2025)
This study aims to analyze the effect of workload and compensation on turnover intention, with job satisfaction serving as a mediating variable. The research was conducted at PT Aerofood ACS Denpasar, a company engaged in catering services, involving a total of 150 employees. The sample size was determined using a non-probability sampling technique with a quota sampling approach to ensure representativeness of the respondents. Data collection was carried out through a structured questionnaire distributed via Google Forms, consisting of 25 measurement items based on a 5-point Likert scale ranging from strongly disagree to strongly agree. This quantitative research design employed both descriptive analysis and inferential statistical testing through Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS 4.0 software. The results of the analysis indicate that workload has a negative and significant influence on job satisfaction, suggesting that higher workload levels tend to reduce employees’ satisfaction with their jobs. On the other hand, compensation demonstrates a positive and significant influence on job satisfaction, indicating that adequate and fair compensation can enhance employees’ feelings of fulfillment and fairness within the organization. Furthermore, job satisfaction is found to have a negative and significant effect on turnover intention, meaning that employees who are more satisfied with their jobs are less likely to develop intentions to leave the company. The mediating test reveals that job satisfaction plays a crucial role in bridging the relationship between workload and turnover intention, as well as between compensation and turnover intention. Specifically, job satisfaction partially mediates the negative impact of workload on turnover intention and the positive impact of compensation on turnover intention. Overall, this research highlights the importance of managing workload effectively and providing fair compensation as strategic efforts to enhance job satisfaction and reduce employees’ tendency to leave the organization.